Virologic and immunologic evidence supporting an association between HHV-6 and Hashimoto's thyroiditis. - Elisabetta Caselli (Public Library of Science (PLoS), 2012)
Hashimoto's thyroiditis (HT) is the most common of all thyroid diseases and is characterized by abundant lymphocyte infiltrate and thyroid impairment, caused by various cell- and antibody-mediated immune processes. Viral infections have been suggested as possible environmental triggers, but conclusive data are not available. We analyzed the presence and transcriptional state of human herpesvirus 6 (HHV-6) in thyroid fine needle aspirates (FNA) and peripheral blood mononuclear cells (PBMCs) from 34 HT patients and 28 controls, showing that HHV-6 DNA prevalence (82% vs. 10%, p≤0.001) and viral load were significantly increased in FNA from HT patients, and thyrocytes from HT FNA displayed a 100-fold higher HHV-6 DNA load compared to infiltrating lymphocytes. In addition, while HHV-6 was strictly latent in positive samples from controls, a low grade acute infection was detected in HT samples. HHV-6 variant characterization was carried out in 10 HT FNA samples, determining that all specimens harbored HHV-6 Variant A.The tropism of HHV-6 for thyroid cells was verified by infection of Nthy-ori3-1, a thyroid follicular epithelial cell line, showing that thyrocytes are permissive to HHV-6 replication, which induces de novo expression of HLA class II antigens. Furthermore, HHV-6-infected Nthy-ori3-1 cells become targets for NK-mediated killing, NK cells from HT patients show a significantly more efficient killing of HHV-6 infected thyroid cells than healthy controls, and HT patients have increased T-cell responses to HHV-6 U94 protein, associated to viral latency. These observations suggest a potential role for HHV-6 (possibly variant A) in the development or triggering of HT.